2019
DOI: 10.1039/c8ra09172b
|View full text |Cite
|
Sign up to set email alerts
|

Berberine nanoparticles for promising sonodynamic therapy of a HeLa xenograft tumour

Abstract: Here we show that berberine (BBR) nanoparticles (BBRNPs, ∼300 nm hydrodynamic diameter) is a promising sonosensitizer for cancer sonodynamic therapy (SDT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, only a few studies have proven the antitumor effects of BBR-PDT ( 15 , 31 , 59 ). The possible reasons are as follows ( 16 ): i) There are multiple factors influencing the photodynamic reactions of BBR; ii) the hydrophobic properties, along with poor stability and bioavailability of BBR limits its application; iii) BBR has high toxicity, particularly when administered by injection; and iv) the light source of BBR-PDT is UV, which has several side effects. such as burn and pain and no advantages compared with other photosensitizers ( 2 ).…”
Section: Biological Effects Of Bbr-mediated Pdtmentioning
confidence: 99%
See 3 more Smart Citations
“…However, only a few studies have proven the antitumor effects of BBR-PDT ( 15 , 31 , 59 ). The possible reasons are as follows ( 16 ): i) There are multiple factors influencing the photodynamic reactions of BBR; ii) the hydrophobic properties, along with poor stability and bioavailability of BBR limits its application; iii) BBR has high toxicity, particularly when administered by injection; and iv) the light source of BBR-PDT is UV, which has several side effects. such as burn and pain and no advantages compared with other photosensitizers ( 2 ).…”
Section: Biological Effects Of Bbr-mediated Pdtmentioning
confidence: 99%
“…The major advantage of SDT compared with PDT is the increased penetration of ultrasound through mammalian tissues compared with light, indicating that it can be used to treat deeper and less accessible tumors ( 61 , 62 ). As the light source of BBR-PDT is UV, which has several side effects, such as burn and pain, BBR-SDT may be a more favorable choice for treating tumors ( 16 ). Wang et al ( 63 ) reported that BBR can enhance ultrasound-induced BSA molecule damage.…”
Section: Biological Effects Of Bbr-mediated Pdtmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to extensive biological activities, such as anti-inflammation, antioxidative, and anti-diabetic, berberine demonstrates anti-tumor activity by means of interference in tumorigenesis and in multiple features of tumor development. Therefore, berberine is widely used in the prevention and treatment of tumors (Refaat et al, 2015;Li et al, 2017a;Liao et al, 2018;Liu et al, 2019a). In addition, it is difficult for berberine to penetrate cytomembrane and to be assimilate into the gastrointestinal tract due to its poor lipid solubility (Lu et al, 2006;Ge et al, 2016;Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%